Literary analysis of the Major Themes Introduced by Nicholas Sparks in his Novels a Walk to Remember, The Notebook, the Guardian, The Wedding, and The Last Song - Valderrama Pinilla, Gloria del Carmen (UDELAS, 2019)
Through writing, people express their thoghts and emotions. Authors have used this means to express feelings in different scenarios. They write what affects tje, om real life. They write what affects them in real life. They create an imaginary world to escape from reallity, and in this way, get rid of their worries and free their souls. Authors have used Literature through drama, poetry, short stories, or novels to fascinate the world by sending their message to the readers. The present work consists of a literay analysis of the themes of love, death and faith introduced by Nocholas Sparks in his novels. A Walk to Remember, The Notebook the Guardina, The Wedding, and the Las song in these novels, the theme of love between characters in fraternal and romantic relations ships are presented in order to demonstrate how magical this feeling can be that can transform people's lives and make us feel immensely happy by changing our lives positevely. Then the analysis of the theme of death is given to prove that no one is exempt from it and that even thought it will take from us the people we love, we must assimilate it as something normal, part of the cycle of life and a means to reach eternity. Then. Then, the theme of faith is introduced to let us know important faith is to get what we want in life if we believe in it. Through this thesis it is demonstrating that lierature is also a good way to express emotions through language.